2018
DOI: 10.1371/journal.pone.0200022
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-mapping and biochemical-modulatory and antioxidant/prooxidant effect of Galium verum extract during acute restraint and dark stress in female rats

Abstract: Galium verum is a well-known medicinal plant which is used in various pathologies. G. verum extracts are characterized here using chromatography, where among the rich pool of phenolic acids of flavonoids two known anti-stress modulators, chlorogenic acid and rutin are identified in high quantities. Additionally, the extracts are characterized using a series of in vitro assays (EPR, DPPH, TPC and TEAC). Considering the chemical findings, the potential beneficial effects of the G. verum extract are explored here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…This extract works efficiently by quenching reactive free radicals [38, 39]. Protein thiol groups are involved in plasma antioxidant reactivities well as in signaling and antioxidant defense and catalysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…This extract works efficiently by quenching reactive free radicals [38, 39]. Protein thiol groups are involved in plasma antioxidant reactivities well as in signaling and antioxidant defense and catalysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have reported the antioxidant potential of G. aparine (Lindsey et al 2002, Bokhari et al 2013. Extracts from the seeds of the G. aparine also have therapeutic effects due to their phytochemical activity (Farcas et al 2018). Since the extraction method used changes the phytochemical component of the extract, it also changes the antioxidant or antidiabetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…80% of the chromatographic area, the four most intense peaks) belong to the cinnamic acid group which present a distinct UV-vis spectrum profile. The assignment of each peak spectrum was also checked using the built-in software (Agilent ChemStation) of the HPLC chromatograph using a house-built-in data base of tens of polyphenolic standards [30]. For this purpose, a score of spectral similarity higher than 90% for any compound (with a given standard) from those three classes was an indication that the tested compound does belong to a certain class.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the oxidative-inflammatory reactions are strongly correlated with the activity of antioxidant enzymes [54]. There are reports that revealed correlations between the level of ROS and the decreased concentrations of antioxidants that lead to the inactivation of endogenous antioxidant enzymes, such as SOD and CAT [15, 30, 55]. In maintaining the proper physiological conditions, those endogenous enzymes play a key role by defending the cells against reactive species.…”
Section: Discussionmentioning
confidence: 99%